Suitable regions for assessing long term trends in lightning activity - Collier, A. B. (2012)
The efficiency and stability of global lightning data are not yet sufficient to provide accurate estimates of long term trends in lightning activity. In contrast, regional lightning networks are generally both efficient and stable. Regions with a low level of interannual variability are well suited to the identification of trends in lightning activity. Satellite lightning data are used to identify countries in South America which display only mild interannual variability. These countries are candidates for regional studies of long term trends in lightning activity. These trends can be linked to climate change.